Pengaruh Self Assessment System dan Pengetahuan Perpajakan Terhadap Tax Evasion pada Wajib Pajak Orang Pribadi : Studi pada Karyawan PT. Ciptajaya Kreasindo Utama (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to test the validity and reliability of the instrument and analyze the effect of the Self-Assessment System and Tax Knowledge on Tax Evasion among employees of PT. Ciptajaya Kreasindo Utama. This study used a quantitative approach with 100 respondents. The validity test was conducted through item-total correlation analysis using SPSS, with the results of all items declared valid because the calculated r value > r table (0.163). The reliability test showed a Cronbach's Alpha value of 0.899 for all variables, indicating a reliable instrument. All classical assumptions (normality, multicollinearity, and heteroscedasticity) were met. The results of multiple linear regression indicate that the Self-Assessment System and Tax Knowledge have a positive and significant effect on Tax Evasion, both partially and simultaneously, with an adjusted R² value of 0.499. The t-test and F-test showed significance below 0.05. The conclusion shows that an increase in both independent variables correlates with an increase in Tax Evasion, indicating the need for an evaluation of the company's internal tax system.